Noninvasive estimation of tumour viability in a xenograft model of human neuroblastoma with proton magnetic resonance spectroscopy ((1)H MRS) - Lindskog, M (Nature Publishing Group, 2003)
The aim of the study was to evaluate proton magnetic resonance spectroscopy ((1)H MRS) for noninvasive biological characterisation of neuroblastoma xenografts in vivo. For designing the experiments, human neuroblastoma xenografts growing subcutaneously in nude rats were analysed in vivo with (1)H MRS and magnetic resonance imaging at 4.7 T. The effects of spontaneous tumour growth and antiangiogenesis treatment, respectively, on spectral characteristics were evaluated. The spectroscopic findings were compared to tumour morphology, proliferation and viable tumour tissue fraction. The results showed that signals from choline (Cho)-containing compounds and mobile lipids (MLs) dominated the spectra. The individual ML/Cho ratios for both treated and untreated tumours were positively correlated with tumour volume (P<0.05). There was an inverse correlation between the ML/Cho ratio and the viable tumour fraction (r=−0.86, P<0.001). Higher ML/Cho ratios concomitant with pronounced histological changes were seen in spectra from tumours treated with the antiangiogenic drug TNP-470, compared to untreated control tumours (P<0.05). In conclusion, the ML/Cho ratio obtained in vivo by (1)H MRS enabled accurate assessment of the viable tumour fraction in a human neuroblastoma xenograft model. (1)H MRS also revealed early metabolic effects of antiangiogenesis treatment. (1)H MRS could prove useful as a tool to monitor experimental therapy in preclinical models of neuroblastoma, and possibly also in children.